2005
DOI: 10.1007/s00125-005-1720-8
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between membrane potential and cytosolic Ca2+ concentration in beta cells from Sur1−/− mice

Abstract: Aims/hypothesis: Islets or beta cells from Sur1 −/− mice were used to determine whether changes in plasma membrane potential (V m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…This study confirmed the lack of first-phase response and showed further that increasing glucose metabolism stimulated insulin release, demonstrating the augmentation pathway (see 67, 68 for review) is intact in the Sur1KO animals. Similar glucosestimulated insulin secretion was reported by Haspel et al [65], and Muñoz et al [105] showed increased insulin release from Sur1KO islets in low glucose plus amino acids. Studies on the Sur1KO animals generated by Shiota et al [137] have usually failed to show insulin secretion under hypoglycemic conditions or a significant increase in secretion when glucose is elevated, thus leading to the conclusion that loss of SUR1 impairs insulin release [41,87], although Eliasson et al [48] reported glucose-stimulated insulin release using this strain.…”
Section: Transgenic Mouse Modelssupporting
confidence: 86%
See 3 more Smart Citations
“…This study confirmed the lack of first-phase response and showed further that increasing glucose metabolism stimulated insulin release, demonstrating the augmentation pathway (see 67, 68 for review) is intact in the Sur1KO animals. Similar glucosestimulated insulin secretion was reported by Haspel et al [65], and Muñoz et al [105] showed increased insulin release from Sur1KO islets in low glucose plus amino acids. Studies on the Sur1KO animals generated by Shiota et al [137] have usually failed to show insulin secretion under hypoglycemic conditions or a significant increase in secretion when glucose is elevated, thus leading to the conclusion that loss of SUR1 impairs insulin release [41,87], although Eliasson et al [48] reported glucose-stimulated insulin release using this strain.…”
Section: Transgenic Mouse Modelssupporting
confidence: 86%
“…Newborn Sur1KO mice were found to exhibit significant hypoglycemia secondary to hyperinsulinemia, but this resolved within several days [133], and the KO animals then remain normoglycemic [65,108,133]. Intraperitoneal glucose tolerance tests on adult mice showed that knockout animals fail to release insulin in response to a glucose challenge [133,137], whereas fasted knockout animals are able to secrete insulin in response to feeding [137] consistent with stimulation via the CNS.…”
Section: Transgenic Mouse Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose appears to inhibit the component of I K,slow admittedly ascribed to K ATP channels [13,15], leading to the hypothesis that it might provide the hyperpolarizing current necessary to terminate the burst. Bursting electrical activity and underlying [Ca 2+ ] i oscillations are nonetheless present in mouse β-cells lacking the SUR1 gene [16][17][18][19], suggesting that channels distinct from the K ATP channel might account in part for physiological bursting and raising the possibility that they might mediate the graded electrical response to glucose. These channels may thus represent significant, albeit undervalued additional targets for glucose action downstream K ATP channel inhibition.…”
mentioning
confidence: 99%